2006
DOI: 10.1111/j.1744-9987.2006.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Volume of the Parathyroid Gland a Predictor of Maxacalcitol Response in Advanced Secondary Hyperparathyroidism?

Abstract: We evaluated the relationship between the volume of parathyroid glands estimated by ultrasonography (US) and response of 22-oxa calcitriol (Maxacalcitol, OCT) in patients with secondary hyperparathyroidism (2HPT) to evaluate whether the volume can be a predictor of the OCT response. Eleven institutes participated in this study. Ninety-four patients with advanced 2HPT were enrolled. The volume of the parathyroid glands were estimated by US before and 6 months after OCT treatment. The response of OCT treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 28 publications
(45 reference statements)
1
40
0
1
Order By: Relevance
“…The conclusion drawn was that the volume of the largest gland as estimated by US could be a useful predictor of the response to OCT in patients with moderate or severe 2HPT. In patients whose glandular volume was less than 300 mm 3 , the OCT was significantly more effective compared with that in patients whose volume was more than 300 mm 3 (19). These results indicated that when a patient has at least one nodular gland, 2HPT may be resistant to medical treatment, including OCT. Volume of parathyroid gland estimated by ultrasonograpy By US it is possible to detect swollen parathyroid glands and measure three dimensions, and to estimate the volume of glands by using the formula (a*b*c* /6) (a,b,c: dimensions of the gland) (20).…”
Section: Pathogenesis Histopathology and Pathophysiology Of 2hptmentioning
confidence: 59%
“…The conclusion drawn was that the volume of the largest gland as estimated by US could be a useful predictor of the response to OCT in patients with moderate or severe 2HPT. In patients whose glandular volume was less than 300 mm 3 , the OCT was significantly more effective compared with that in patients whose volume was more than 300 mm 3 (19). These results indicated that when a patient has at least one nodular gland, 2HPT may be resistant to medical treatment, including OCT. Volume of parathyroid gland estimated by ultrasonograpy By US it is possible to detect swollen parathyroid glands and measure three dimensions, and to estimate the volume of glands by using the formula (a*b*c* /6) (a,b,c: dimensions of the gland) (20).…”
Section: Pathogenesis Histopathology and Pathophysiology Of 2hptmentioning
confidence: 59%
“…Moreover, the response to vitamin D sterols is substantially reduced once parathyroid hyperplasia has progressed to the advanced nodular form, presumably because of the reduced expression of calcium-sensing receptors (CaSR) and vitamin D receptors (VDR) (6 -10). Several clinical studies suggest that parathyroid gland volume in excess of 500 mm 3 , as evaluated by ultrasonography, appears to be a useful indicator of responsiveness to vitamin D therapy (11)(12)(13). This concept is supported by the observation that surgically removed parathyroid glands weighing Ͼ500 mg usually exhibit nodular formations (3).…”
mentioning
confidence: 58%
“…It is well known that, in patients with SHPT, the presence of parathyroid enlargement is a major determinant of response to treatment with vitamin D sterols (11)(12)(13). This finding is attributed to the observation that most of the enlarged glands removed from severe SHPT patients exhibit a nodular pattern of hyperplasia and decreased VDR expression (6,9,10), which could render the parathyroid glands less responsive to the biologic actions of vitamin D. In contrast, the present study showed that treatment with cinacalcet, an allosteric activator of the CaSR, is effective in suppressing PTH secretion even in patients with enlarged glands, in which the expression of CaSR is likely to be markedly decreased (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…The failure of medical therapy is primarily due to progressive downregulation (8, 9, 10) of both calcium-sensing receptors (CaSR) and vitamin D receptors (VDR) (4,11,12,13). Actually, it is widely acknowledged that the PTG volume (maximum diameter O10 mm or volume O500 mm 3 ) negatively influences the response to calcitriol or vitamin D analog treatment (14,15). In these cases, parathyroidectomy (PTx) may be indicated (16).…”
Section: Introductionmentioning
confidence: 99%